Profiling the motivational characteristics of Greek university students. (December 2021) - Kantaridou, Zoe; Machili, Ifigeneia; Papadopoulou, Iris
Abstract: Research in L2 motivation of the past 60 years has gone through a journey from seeking the sources of motivation within the individual to currently locating motivation at the interplay of cognitive, affective, and social parameters. This study adopts Dörnyei's (2005) L2 Motivational Self System and employs an adapted version of Taguchi et al.'s (2009) questionnaire in order to examine Greek university students' motivational profiles with regard to ideal L2 self and ought-to L2 self and promotion and prevention instrumentality. In the cluster analysis three motivational clusters are identified, with prevention instrumentality and ideal L2 self as main distinguishing factors. Through a series of analyses of variance and crosstabulation the three clusters are associated with language-related, future goals and social variables: The emergent clusters are: the highly motivated students also most proficient in L2, the low motivated students also least proficient in L2 and the overstrivers. Promotion orientations (ideal L2 self and instrumentality promotion) lead to higher L2 proficiency that lasts longer while prevention orientations erode it. The study compares Greek university students' actual achievement to self-perceived competence and highlights the importance of the two regulatory orientations for the study of L2 motivation.